THE ARCTIC: A DIALOGUE FOR DEVELOPMENT - Yury Mazurov; Vladimir Tikunov (Geography, Environment, Sustainability, 2010)
In September 2010, Moscow hosted the International Arctic Forum “The Arctic—Territory of Dialogue.” The Arctic Forum focused its attention on elements of sustainable development in the Arctic region, i.e., ecology, economics, infrastructure, social services, security, and geopolitics. Many Russian experts and many well-known politicians and experts from leading research centers of the Arctic countries (Canada, Denmark, Finland, Iceland, Norway, Sweden, and USA), as well as by participants from France, Germany, Netherlands, and other countries attended the forum. Scholars and public figures from the European countries, representatives of the NATO, the Organization for Security and Cooperation in Europe and other institutions were also present at the conference. In his key-note speech the Chairman of the Board of Trustees of the Russian Geographical Society (RGS), Prime Minister of the Russian Federation, Vladimir V. Putin formulated the principles of Russian national policy in the Arctic. Russian and foreign participants supported the idea of continuing dialogue on the Arctic under the RGS’s aegis and the transformation of the Arctic Forum into a permanent platform for discussions on the most urgent issues of the region.